Breaking barriers: The digital revolution in girls education across India - Abhisek Panda; Gope, Laxmiram (Journal of interdisciplinary studies in education, 2024)
This theoretical research article looks into the necessity of embracing digital pedagogy as a transformative force for girls' education in contemporary India. This study is grounded in three main objectives: (1) assessing the current state of girls’ education in India, (2) exploring the potential benefits of digital pedagogy, and (3) understanding the challenges in implementing digital pedagogy. This study aims to unravel the unique dynamics surrounding the educational landscape for girls. Through a comprehensive analysis of the literature and theoretical frameworks, this article seeks to illuminate how digital pedagogy can catalyze girls' empowerment, addressing the multifaceted challenges that hinder their educational advancement.